2017
DOI: 10.4274/cayd.86580
|View full text |Cite
|
Sign up to set email alerts
|

Central Line-Associated Bloodstream Infections in Pediatric Intensive Care Unit

Abstract: Introduction:The aim of this study was to determine the frequency of central line-associated bloodstream infections, risk factors, their relationship with catheter insertion location, and the effect of central line-associated bloodstream infections on mortality and pediatric intensive care unit (PICU) length of stay. Methods: This was a prospective, observational and cohort study, carried out between November 2009 and February 2011. During this period, all the patients who had central-line were monitored for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
1
9
2
1
Order By: Relevance
“…According to our study, the sample's median age was 12 months (IQR 4 to 72). It is lower than many other published data points [62][63][64], and men dominate, as they do in most research papers [64]. Furthermore, the CRBSI rate is noteworthy because it's higher than a few [62,65] but lower than the majority of the research articles [63,64,[66][67][68] In addition, we observed a CRBSI rate of 4.10 for 1463 central line days, but we predicted 1.902 for the same days.…”
Section: Discussioncontrasting
confidence: 74%
“…According to our study, the sample's median age was 12 months (IQR 4 to 72). It is lower than many other published data points [62][63][64], and men dominate, as they do in most research papers [64]. Furthermore, the CRBSI rate is noteworthy because it's higher than a few [62,65] but lower than the majority of the research articles [63,64,[66][67][68] In addition, we observed a CRBSI rate of 4.10 for 1463 central line days, but we predicted 1.902 for the same days.…”
Section: Discussioncontrasting
confidence: 74%
“…35 Similarly, a Turkish study showed a mean duration of central line use among the studied population 14 AE 9.7 days. 36 An amazing finding was reporting a zero MDRO identified among the isolated pathogens in the post-intervention phase. Other investigations, however, done in Egypt, Greece, Turkey, and Brazil, have not revealed such results, demonstrating that the majority of the organisms isolated were gram-negative, with a significant percentage of these organisms being MDRO.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations, however, done in Egypt, Greece, Turkey, and Brazil, have not revealed such results, demonstrating that the majority of the organisms isolated were gram-negative, with a significant percentage of these organisms being MDRO. 21,26,34,36 This achievement greatly impacted patients' management and duration of ICUs stay not only on those developed infection but also on all admitted patients as the good practice and compliance extended everywhere. The current study found that, despite the fact that our intensive care units are unique in terms of patient characteristics and serve the entire country, the team was able to review the need for central lines, prompt removal of unnecessary lines, reduce the duration of central line use, and, as a result, the CLABSI rate.…”
Section: Discussionmentioning
confidence: 99%
“…22 Santral venöz kateter ilişkili KDE hastane ilişkili enfeksiyonların önemli nedenlerindendir. 23 Çalışmamızda SVK takılan ve mekanik ventilasyon uygulanan hastalarda daha sık nozokomiyal KDE saptanmıştır. Elward ve Fraser'in 14 aynı anda birden fazla SVK kullanımının KDE riskini daha da artırdığını bildirmiştir.…”
Section: Discussionunclassified